Novel IL2RG gene mutation causing primary combined immunodeficiency disease: A case report and literature review - Fang Cao; Yingyu Shi; Fang Deng; Yu Yan (Central European Journal of Immunology)
This study presents a detailed clinical case of a 10-year-old boy with a history of prolonged cough, fever, and delayed diagnosis of bronchiectasis. Review of the case revealed that the child has had recurrent bronchitis, otitis media, skin allergies, and viral warts since early childhood, indicating persistent immune system abnormalities. Imaging studies, including pulmonary and sinus CT scans, show significant bronchiectasis accompanied by infections and sinusitis. Immunological assessment revealed abnormalities in immunoglobulin levels and T-cell distribution, suggesting a potential immune deficiency. Whole exome sequencing did not identify any genetic variants highly associated with and definitively pathogenic for bronchiectasis but detected a compound heterozygous missense mutation c.420A>T (p.R140S) in the IL2RG gene, linked to primary combined immunodeficiency (CID), a clinical phenotype rarely reported in China due to this gene mutation. This case report not only enhances our understanding of CID but also provides a new addition to the genetic landscape of CID both domestically and internationally, aiding in earlier diagnosis and treatment of such diseases in clinical practice. During the 18-month follow-up period, the child was unable to participate in physical activities, and experienced recurrent rhinitis, sinusitis, and warts. The child’s current weight and height are 30 kg and 140 cm, respectively.